The Bradykinin System Contributes to the Regulation of Prostaglandin-Endoperoxide Synthase 2 Expression in Human Amnion Fibroblasts: Implications for Term and Preterm Birth - Ni, Xiao-tian; Wang, Wang-sheng; Liu, Yun; Lin, Yi-kai; Zhang, Fan; Lei, Wen-jia; Ling, Li-jun; Pan, Fan; Zhu, Ya-nan; Li, Meng-die; Duan, Tao; Liu, Ming; et al. (Frontiers in Endocrinology, 2022)
Background: Bradykinin (BK) and its biologically active metabolite des-Arg9 bradykinin (DABK) play a pivotal role in inflammation. Since chorioamnionitis is the leading cause of preterm birth and prostaglandin E2 (PGE2) derived from the amnion is key to labor initiation, we investigated if bradykinin peptides are part of the regulatory network of PGE2 synthesis in human amnion at parturition. Methods: Human amnion tissue was obtained from term and preterm birth for the study of changes of bradykinin system at parturition. Cultured primary human amnion fibroblasts, the major source of PGE2, were used to study the effects of bradykinin peptides on PTGS2 expression and PGE2 production as well as the effects of infection mediators on bradykinin receptors. Results: Bradykinin peptides and their receptors BDKRB1 and BDKRB2 were present in human amnion, and their abundance increased in term and preterm labor. However, transcripts of the genes encoding the bradykinin precursor and its proteolytic cleavage enzymes were hardly detectable in human amnion despite of increased abundance of bradykinin peptides in term and preterm labor, suggesting that there is an alternative source of bradykinin peptides for human amnion and their actions are enhanced in human amnion at parturition. In vitro studies in cultured human amnion fibroblasts showed that both BK and DABK increased the expression of prostaglandin-endoperoxide synthase 2 (PTGS2), the rate-limiting enzyme in prostaglandin synthesis, and subsequent PGE2 production. These effects of BK and DABK were mediated through BDKRB2 and BDKRB1 receptors respectively with subsequent activation of the p38 and ERK1/2 pathways. Moreover, lipopolysaccharide (LPS) and serum amyloid A1 (SAA1), the important mediators of infectious inflammation, induced the expression of both BDKRB1 and BDKRB2 through toll-like receptor 4 (TLR4). Induction of BDKRB1 and BDKRB2 expression by LPS and SAA1 enhanced BK- or DABK-induced PTGS2 expression and PGE2 production in human amnion fibroblasts. Conclusions: This study demonstrated for the first time that the human amnion is a target tissue of bradykinin peptides, and the bradykinin system may be part of the regulatory network of PTGS2 expression and PGE2 production in human amnion fibroblasts at both term and preterm birth, which may be enhanced by infection.